A Practical Cryopreservation and Staining Protocol for Immunophenotyping in Population Studies. Issue 1 (16th April 2018) - Barcelo, Helene; Faul, Jessica; Crimmins, Eileen; Thyagarajan, Bharat
Abstract: Large population‐based cohort studies, through their prospective collection of a broad range of health information, represent an invaluable resource for novel insights into the pathogenesis of human diseases. Collection and cryopreservation of viable cells from blood samples is becoming increasingly common in large cohorts as these cells are a valuable resource for immunophenotyping and functional studies. The cryopreservation of peripheral blood mononuclear cells (PBMCs), thawing, and immunophenotyping protocols used to immunophenotype 9938 participants in the Health and Retirement Study (HRS) are described. The extensive quality control involved in a large‐scale immunophenotyping epidemiological study is also outlined. The existing literature on the effect of cryopreservation on various immune cell subsets including T, B, NK cells, monocytes, and dendritic cells is provided. © 2018 by John Wiley & Sons, Inc.